Case Report: Metastatic involvement of the acromioclavicular joint in a patient with papillary carcinoma of the ureter - Türemiş, Cihangir; Çeltik, Mustafa; Erduran, Mehmet (Frontiers in Surgery, 2025)
Ureteral papillary carcinoma is a rare subtype of urothelial carcinoma, ranking fourth among cancers following prostate (or breast) cancer, lung cancer, and colorectal cancer. Although previous studies have documented bone metastases mainly in the pelvis, spine, ribs, and femur, this case report presents the first recorded instance of metastasis occurring in the acromioclavicular joint. A 62-year-old woman with a history of left flank pain and macroscopic hematuria underwent a left nephroureterectomy, which revealed ureteral papillary carcinoma. Three years later, she reported left shoulder pain, leading to the discovery of a metastatic lesion in the distal clavicle. Approximately 9 cm of metastatic bone was resected while preserving nearby nerve and vascular structures. The resulting bone defect was grafted with a 9-cm bone graft removed from the middle third of the fibula. This case report underscores the importance of considering distant metastases, even in atypical locations, in patients with ureteral papillary carcinoma and aims to share the entire treatment journey and insights gained.